Structural Optimization and Cutting Simulation Analysis of BAT Deep-hole Drilling - WU Xue-feng; MA Lu; YUAN Zhong-liang; YANG Shu-cai (Journal of Harbin University of Science and Technology)
BAT deep-hole drill is a typical inner-chip removal drill. Structures and angles of tools are the main factors that influence the machining quality and machining efficiency. Because the processing of deep-hole drilling is not visible，it is very difficult to optimize structure and angles of tool through the experiment method. In this paper，finite element method is used as follows: static analysis and modal analysis of BAT deep-hole drill are built by ANSYS，and then the deformation and six-set vibration mode diagram of BAT deep-hole drill are carried out as a reference for structural optimization of BAT deep-hole drilling; Drilling process model of each tool tooth is built by AdvantEdge，and the effect of chip formation process and tool angles on cutting force and torque are studied as reference for tool angle optimization.